Sinking the ships : Indonesia's foreign policy under Jokowi - B. A. Hamzah (2015)
Despite some adverse comments, President Joko Widodo is not about to drastically change Indonesia's "free and active foreign policy". What may change during his tenure is the emphasis, orientation and strategy. His challenge is how to exucute his foreign policy without losing friends.Jokowi should start calling on his ASEAN counterparts to continue the traditional regional diplomacy.